THE EFFECT OF FINANCIAL LITERACY AND FINANCIAL ATTITUDE ON THE USE OF DIGITAL WALLETS AMONG STUDENTS IN SURAKARTA CITY - Brian Sutatama Kusumapradana; Siti Aisyah (Magister Akuntansi, Universitas Atma Jaya Makassar, 2022)
This research aims to determine the effect of financial literacy and financial attitude on the use of digital wallets among students in Surakarta City. This research is a quantitative research using primary data. Sampling was obtained by non-probability sampling method with purposive sampling technique. The sample used in this research was 100 students in the city of Surakarta. Research data obtained from the collection of questionnaires. The data analysis technique used in this research is multiple linear regression analysis. The results showed that (1) Financial Literacy and Financial Attitude had a positive effect on the Use of Digital Wallets among students, and (2) Financial Literacy and Financial Attitude together had a positive effect on the Use of Digital Wallets among students in Surakarta.